Sistem Pakar Pencarian Silsilah Keluarga Menggunakan Pemrograman Prolog - Dwi Retnoningsih (Universitas Sahid Surakarta, 2010)
Family tree search process for someone who is a member of the family would quickly be known. But instead for someone other than a family member would be adifficult thing to do if you do not know with certainty the origin of the family. The purpose of this study is making an expert system application to search the familytree using Prolog Language. The research method that I use is the method of back tracking. This research resulted in an expert system for searching the family tree.